PROPUESTA PARA LA CREACIÓN DE NUEVOS PRODUCTOS FINANCIEROS PARA LA COOPERATIVA DE AHORRO Y CRÉDITO OBRAS PÚBLICAS FISCALES DE LOJA Y ZAMORA - Jara Chicaíza, David Mauricio (2019)
The purpose of this research topic is to OFFER A NEW PROPOSAL OF FINANCIAL PRODUCTS FOR THE SAVING AND CREDIT COOPERATIVE PUBLIC WORKS OF LOJA Y Zamora, which is aimed at providing solutions and helping to satisfy the needs of the members of the entity, and at the same time give the cooperative a strategy that allows it to be more competitive in the market that works and diversify its range of products in order to generate greater economic value to the entity. The purpose of this research topic is to offer a NEW PROPOSAL OF FINANCIAL PRODUCTS FOR THE SAVING AND CREDIT COOPERATIVE PUBLIC WORKS OF LOJA Y Zamora, which is aimed at providing solutions and helping to satisfy the needs of the members of the entity, and at the same time give the cooperative a strategy that allows it to be more competitive in the market that works and diversify its range of products in order to generate greater economic value to the entity. In order to comply with the specific objectives of the thesis work, we began with the situational diagnosis of the Cooperative, which allowed us to know how it is structured in an administrative way, its institutional philosophy and the financial products it currently offers. Within this diagnosis, a financial analysis was also carried out with the objective of knowing its solvency, asset quality, liquidity and profitability through its results, demonstrating the financial situation maintained by the entity. In the same way, an analysis of the competition was made, that is to say, of all those Savings and Credit Cooperatives that are in the city of Loja that are in the segment 4, with the purpose of knowing which are the financial products that it offers to the market, as also surveys were applied to the members of the cooperative, with the objective of knowing their opinions and their necessities regarding the financial products that the entity offers, and that they would like that they believe in the same one; and finally an interview was made to the manager of the entity to know the importance and benefit of the proposal for the Cooperative. Then, with the data obtained from the surveys, we proceeded to develop the proposal with the financial products most demanded by the partners, such proposal consists of background, justification, objectives and development of each product, within them